(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This exploration delves into the intricacies of Res Judicata, focusing on case laws,exceptions, and restatements as elucidated by the Supreme Court of India. Acknowledging thesignificant role of amendments in law, particularly within sections like Property or Tax, the essayhighlights the limited understanding of the aims, timing, and methods of these amendments within thelegal profession.Emphasizing that the Res Judicata rule outlined in Section 11 of the Code of Civil Procedure does notcover every situation, the essay discusses the rights guaranteed to the plaintiff under Article 32 and 226.The Latin phrase Res Judicata is examined, pointing out its implications as something adjudicated,resolved, or settled by judgments. The complexity of executing an unfavorable decree is analyzed,presenting both benefits and risks.The metaphysical and philosophical dimensions of res judicata are explored, relating it to the quality ofsentences, beliefs, and thoughts in contemporary usage. The essay delves into the universal presence ofres judicata in jurisprudence, grounded in public policy, necessity, and preventing hardship onindividuals.Highlighting the promotion of judgment finality to prevent the abuse of justice, the essay navigatesthrough instances where Res Judicata intersects with Fundamental Rights, bringing attention to thenuanced interpretation of legal terms. The exceptions to Res Judicata are examined, playing a crucialrole in cases with clear rules and potential disputes over claims.While acknowledging the demerits of Res Judicata, the essay presents merits such as preventinginjustice through selective flexibility, preserving parties’ rights, discouraging forum shopping, andsimplifying procedural complexities. The principle’s role in maintaining justice and ensuring fairness insubsequent litigation is analyzed, emphasizing the multifaceted nature of Res Judicata within the legalframework.